The teenager's perception of parenting - Padayachy, Narissa Domitilla (Department of Psychology, 2024)
[Pages missing] The institution of the family presents itself as a subject of intense and controversial public concern. Not only has it received heightened attention from academics and policy makers recently, but also from the popular media and the public at large. Furthermore, issues of child and family welfare which are being illuminated in the Reconstruction and Development Programme in South Africa, all emphasise the importance that society places on strong families which in turn can build stronger communities.